2002
DOI: 10.1038/sj.ijir.3900801
|View full text |Cite
|
Sign up to set email alerts
|

Activators of soluble guanylate cyclase for the treatment of male erectile dysfunction

Abstract: Soluble guanylate cyclase (sGC) is an important enzyme in corpus cavernosum smooth muscle cells as it is one of the regulators of the synthesis of cGMP. The efficacy of sildenafil (Viagra TM ) in the treatment of male erectile dysfunction indicates the importance of the cGMP system in the erectile response as the increased levels of cGMP induce relaxation of the corpus cavernosum. sGC is physiologically activated by nitric oxide (NO) during sexual stimulation, and its activity can be pharmacologically enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 49 publications
0
26
0
2
Order By: Relevance
“…[7][8][9][10] Some drugs such as inhibitors of PDE 5 or other vasodilators, which can promote the relaxation of corpus cavernosum smooth muscle, can be potentially used to treat ED. [11][12][13][14][15][16][17][18][19] It has been shown that there are many Chinese traditional herbals that can enhance sexual activity. [20][21][22][23][24] Recently, there is an increasing interest in investigating their effective components.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Some drugs such as inhibitors of PDE 5 or other vasodilators, which can promote the relaxation of corpus cavernosum smooth muscle, can be potentially used to treat ED. [11][12][13][14][15][16][17][18][19] It has been shown that there are many Chinese traditional herbals that can enhance sexual activity. [20][21][22][23][24] Recently, there is an increasing interest in investigating their effective components.…”
Section: Introductionmentioning
confidence: 99%
“…Although sildenafil is generally an efficacious agent for the treatment of ED, this drug has limited efficacy in a subpopulation of ED patients, e.g., diabetics. A PDE5 inhibitor cannot increase cGMP levels by itself unless there is release of NO that activates guanylate cyclase to increase cGMP levels (35). In this situation, PDE5 inhibitors can maintain cGMP levels by blocking the metabolism of cGMP.…”
Section: Figmentioning
confidence: 99%
“…5,7,9 The chambers were perfused with modified Krebs' solution at a constant flow of 1.0 ml/min by means of peristaltic pumps (Miniplus 2, Gilson). One end of the preparation was tied to a Grass FT 03C forcedisplacement transducer connected to a Linearcorder WR 3101 (Graphtec, Tokyo, Japan) for the registration of isometric changes in tension.…”
Section: Functional Studiesmentioning
confidence: 99%
“…NO-independent soluble guanylate cyclase (sGC) activators (BAY41-2272) and an NO-releasing derivative of sildenafil (sildenafil nitrate; NCX-911) are two such potential approaches to the medical management of ED. 8,9 Although the rat is an excellent model for diabetes research, our experience with its penile corpus cavernosum is that it is a difficult tissue to work with (ie spontaneous contractions and the size of the tissue) compared to the anococcygeus muscle. Anococcygeus and retractor penis muscles have been widely accepted as ideal smooth muscle models to study not only nitrergic neurotransmission but also other nonadrenergic noncholinergic neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%